2012
DOI: 10.1136/gutjnl-2011-301957
|View full text |Cite
|
Sign up to set email alerts
|

TheNOD2insC polymorphism is associated with worse outcome following ileal pouch-anal anastomosis for ulcerative colitis

Abstract: Genetic polymorphisms, in particular, the NOD2insC risk allele, are associated with chronic inflammatory pouch outcomes among patients with UC and IPAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 45 publications
2
44
1
Order By: Relevance
“…The presence of gene alterations reflecting inflammatory processes in the proximal SB of pouch patients resembles the subtle inflammatory changes seen in the non-involved bowel mucosa of CD patients. This, taken together with the fact that gene expression alterations within the pouch of UC patients are comparable to the alterations seen in CD ileitis11 and the finding that NOD 2insC polymorphism (which is specific to CD) is associated with pouchitis,12 further support our hypothesis that pouchitis in UC patients is a CD-like IBD. The fact that there are more gene expression alterations in the pouch itself, as well as in the proximal SB among the CLDP patients compared with the CP patients, supports the uniqueness of this phenotype.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The presence of gene alterations reflecting inflammatory processes in the proximal SB of pouch patients resembles the subtle inflammatory changes seen in the non-involved bowel mucosa of CD patients. This, taken together with the fact that gene expression alterations within the pouch of UC patients are comparable to the alterations seen in CD ileitis11 and the finding that NOD 2insC polymorphism (which is specific to CD) is associated with pouchitis,12 further support our hypothesis that pouchitis in UC patients is a CD-like IBD. The fact that there are more gene expression alterations in the pouch itself, as well as in the proximal SB among the CLDP patients compared with the CP patients, supports the uniqueness of this phenotype.…”
Section: Discussionsupporting
confidence: 79%
“…One possibility is that the genetic background may play a role. Indeed, the NOD2insC (rs2066847) risk variant was found to be associated with the development of pouchitis among UC patients,12 and this mutation is clearly associated with CD,13 and not UC. The resemblance of pouchitis to CD may suggest that, as in CD, UC patients with pouchitis could have an inflammatory disease that is not exclusive to the pouch.…”
Section: Introductionmentioning
confidence: 99%
“…The pediatric and healthy control cohorts along with strict quality-control measures were carried out as described previously for this cohort. 12,27 Variables Constructs and Antibodies. Myc-tagged human p67 phox complementary DNA was cloned into the pCDNA3 vector (Invitrogen, Carlsbad, CA), as described previously 12 ; green fluorescent protein (GFP)-tagged human p40 phox complementary DNA was obtained from the laboratory of Dr John Brumell and GFP-tagged human p47 phox complementary DNA was obtained from OriGene (pCMV6-AC-GFP, RG201233).…”
Section: Methodsmentioning
confidence: 99%
“…In support of this assumption, it is observed that pouchitis only occurs after restoration of the fecal stream through the pouch [19,20]. In addition, a dysbiosis in pouchitis has been documented [21], and several genes associated with the innate immune response and microbial sensing and recognition have been associated with an increased risk for pouchitis, including the NOD2/CARD15 gene [22,23], IL-1 receptor antagonist gene [24] and Toll-like receptor genes [25].…”
mentioning
confidence: 77%